Walking Exercises for Diabetes Mellitus Patients with Unstable Blood Glucose Levels: Case Report - Purwanti, Lina Ema; Roissah, Dinatur; Mas’udah, Anni Fithriyatul (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2025)
Controlling blood sugar levels is the key to the treatment program by reducing weight, diet, and exercise. Physical activity is one factor affecting glycemic management for Diabetes Mellitus (DM) patients. This case study aims to maintain the stability of blood sugar levels in DM patients by applying walking exercises. The design of this research is a case report with a nursing process approach carried out on Diabetes Mellitus patients with nursing problems of unstable blood sugar levels. The Bendo Community Health Center carried out nursing care for seven days. The intervention implemented is walking exercises. The case study results are presented in the form of nursing documentation. The case study results showed that the patient's blood sugar levels tended to be stable starting on the second day of the intervention. An increase in whole-body insulin sensitivity mostly explains exercise-induced glycemic control. The long-term advantages of frequent exercise on glycemic control are related to the cumulative effect of transitory gains in insulin sensitivity and glycemic control after each bout of exercise rather than structural changes in insulin sensitivity.